High-dose chemotherapy with autologous haemopoietic stem cell transplantation for newly diagnosed primary CNS lymphoma: a prospective, single-arm, phase 2 trial. Issue 8 (August 2016) - Illerhaus, Gerald; Kasenda, Benjamin; Ihorst, Gabriele; Egerer, Gerlinde; Lamprecht, Monika; Keller, Ulrich; Wolf, Hans-Heinrich; Hirt, Carsten; Stilgenbauer, Stephan; Binder, Mascha; Hau, Peter; Edinger, Matthias; et al.
Summary: Background: High-dose methotrexate-based chemotherapy is standard for primary CNS lymphoma, but most patients relapse. High-dose chemotherapy with autologous stem cell transplantation (HCT-ASCT) is supposed to overcome the blood–brain barrier and eliminate residual disease in the CNS. We aimed to investigate the safety and efficacy of HCT-ASCT in patients with newly diagnosed primary CNS lymphoma. Methods: In this prospective, single-arm, phase 2 trial, we recruited patients aged 18–65 years with newly diagnosed primary CNS lymphoma and immunocompetence, with no limitation on clinical performance status, from 15 hospitals in Germany. Patients received five courses of intravenous rituximab 375 mg/m 2 (7 days before first high-dose methotrexate course and then every 10 days) and four courses of intravenous high-dose methotrexate 8000 mg/m 2 (every 10 days) and then two courses of intravenous rituximab 375 mg/m 2 (day 1), cytarabine 3 g/m 2 (days 2 and 3), and thiotepa 40 mg/m 2 (day 3). 3 weeks after the last course, patients commenced intravenous HCT-ASCT (rituximab 375 mg/m 2 [day 1], carmustine 400 mg/m 2 [day 2], thiotepa 2 × 5 mg/kg [days 3 and 4], and infusion of stem cells [day 7]), irrespective of response status after induction. We restricted radiotherapy to patients without complete response after HCT-ASCT. The primary endpoint was complete response at day 30 after HCT-ASCT in all registered eligible patients who received at least 1 day of study treatment. This trial is registered atClinicalTrials.gov, numberNCT00647049 . Findings: Between Jan 18, 2007, and May 23, 2011, we recruited 81 patients, of whom two (2%) were excluded, therefore we included 79 (98%) patients in the analysis. All patients started induction treatment; 73 (92%) commenced HCT-ASCT. 61 (77·2% [95% CI 66·1–86·6]) patients achieved a complete response. During induction treatment, the most common grade 3 toxicity was anaemia (37 [47%]) and the most common grade 4 toxicity was thrombocytopenia (50 [63%]). During HCT-ASCT, the most common grade 3 toxicity was fever (50 [68%] of 73) and the most common grade 4 toxicity was leucopenia (68 [93%] of 73). We recorded four (5%) treatment-related deaths (three [4%] during induction and one [1%] 4 weeks after HCT-ASCT). Interpretation: HCT-ASCT with thiotepa and carmustine is an effective treatment option in young patients with newly diagnosed primary CNS lymphoma, but further comparative studies are needed. Funding: University Hospital Freiburg and Amgen.